THE MORMON STORY. - Bushman, Richard Lyman (Fides et historia, 2012)
The article focuses on Mormon history, with an emphasis on why Mormonism changed from being radical in the 19th century to being conservative in the 20th century. The author provides a brief historical background of radical Mormonism, including the unconventional Christian theology of American religious leader and founder of the Latter Day Saint (LDS) movement Joseph Smith, the establishment of communal orders and cooperatives In Utah by LDS leader Brigham Young and Young's practice of polygamy in Utah. The author explores the various aspects of the shift to Mormon conservatism, including the renouncement of Mormon polygamy in 1890, their embracing of free enterprise and capitalism and their moving from villages to cities in the 20th century.